Combinatorial genetic manipulation of Cx50, PI3K and PTEN alters postnatal mouse lens growth and homeostasis - Sellitto, Caterina; White, Thomas W. (Frontiers in Ophthalmology, 2025)
IntroductionPhosphoinositide 3-kinase (PI3K), Phosphatase and tensin homolog (PTEN) and connexin50 (Cx50) have individually been shown to play critical roles in the growth, development and maintenance of the lens and to functionally interact in vitro. To elucidate how gap junctional coupling mediated by Cx50 and intracellular signaling mediated by PI3K and PTEN synergistically interact to regulate lens homeostasis in vivo, we generated and characterized double knockout animal models lacking the p110α subunit of PI3K and Cx50, or PTEN and Cx50.MethodsWe interbred lens specific p110α and PTEN conditional knockout animals with Cx50 deficient mice to generate double knockouts. Animals and eyes were weighed, lenses were dissected, photographed, measured, fixed and sectioned for histological analysis. Lens epithelial cell proliferation was determined using 5-ethynyl-2’-deoxyuridine (EdU) labeling.ResultsDouble knockout of p110α and Cx50 led to a significant reduction in lens and eye size, and a high rate of lens rupture. The individual cell proliferation defects of the Cx50 and p110α single knockout lenses both persisted in the double KO. Double deletion of Cx50 and PTEN produced severe lens defects, including cataract, aberrant cell migration, altered cell proliferation, vacuole formation and lens rupture.ConclusionThe severe phenotypes in p110α/Cx50 and PTEN/Cx50 double deficient lenses suggest that PI3K, PTEN and Cx50 participate in both distinct and common regulatory pathways that are necessary to maintain normal lens growth and homeostasis.